2014
DOI: 10.1021/mp500201s
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Polymers on the Precipitation Behavior of Highly Supersaturated Aqueous Danazol Solutions

Abstract: The phase behavior of supersaturated solutions of a relatively hydrophobic drug, danazol, was studied in the absence and presence of polymeric additives. To differentiate between phase separation to a noncrystalline phase and phase separation to a crystalline phase, an environmentally sensitive fluorescent probe was employed. Induction times for crystallization in the presence and absence of polymeric additives were studied using a combination of ultraviolet and fluorescence spectroscopy. It was found that, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 49 publications
1
54
0
Order By: Relevance
“…From the fluorescence studies, it is apparent that the second phase formed is noncrystalline, as it has been previously shown that the fluorescent dyes cannot partition into the crystalline phase, and the optical properties of the dye in the presence of crystalline material are similar to those in the aqueous environment. 43 LLPS concentrations as determined by fluorescence experiments at different pHs are shown in Figure 3. There is an excellent agreement between the LLPS concentration obtained from UV experiments and that obtained using fluorescence.…”
Section: Molecular Pharmaceuticsmentioning
confidence: 99%
“…From the fluorescence studies, it is apparent that the second phase formed is noncrystalline, as it has been previously shown that the fluorescent dyes cannot partition into the crystalline phase, and the optical properties of the dye in the presence of crystalline material are similar to those in the aqueous environment. 43 LLPS concentrations as determined by fluorescence experiments at different pHs are shown in Figure 3. There is an excellent agreement between the LLPS concentration obtained from UV experiments and that obtained using fluorescence.…”
Section: Molecular Pharmaceuticsmentioning
confidence: 99%
“…Immediately upon contact with aqueous medium, amorphous drug usually dissolves much more rapidly compared with crystalline dose forms, due to the absence of crystal lattice, and the existence of water-soluble polymers. The solution drug concentration usually reaches various supersaturations depending on the physiochemical properties of the drug and the ASD formulation design (10)(11)(12)(13)(14). The initial drug dissolution is vividly termed as Bspring^ (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…There are some reports available regarding formulation strategies that can be applied to inhibit in vivo precipitation. [29][30][31][32][33] The cannabinoid receptor 1 antagonists AZD1175 and AZD2207 are highly lipophilic weak bases with low pH-dependent solubility and high intestinal permeability in the Caco-2 model ( Fig. 1 and Table 1).…”
Section: Introductionmentioning
confidence: 99%